2006
DOI: 10.1007/s10703-006-0031-0
|View full text |Cite
|
Sign up to set email alerts
|

HySAT: An efficient proof engine for bounded model checking of hybrid systems

Abstract: In this paper we present HySAT, a bounded model checker for linear hybrid systems, incorporating a tight integration of a DPLL-based pseudo-Boolean SAT solver and a linear programming routine as core engine. In contrast to related tools like MathSAT, ICS, or CVC, our tool exploits the various optimizations that arise naturally in the bounded model checking context, e.g. isomorphic replication of learned conflict clauses or tailored decision strategies, and extends them to the hybrid domain. We demonstrate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 36 publications
0
72
0
Order By: Relevance
“…This integration is prototypical, lacking any optimizations like reuse of inferences along the isomorphic copies of the transition relation in a BMC problem [6]. Given the extremely high computational cost of computing an interval enclosure of an ODE, such mechanisms for copying inferences across isomorphic sub-formulae rather than recomputing them should provide large speedups.…”
Section: First Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This integration is prototypical, lacking any optimizations like reuse of inferences along the isomorphic copies of the transition relation in a BMC problem [6]. Given the extremely high computational cost of computing an interval enclosure of an ODE, such mechanisms for copying inferences across isomorphic sub-formulae rather than recomputing them should provide large speedups.…”
Section: First Experimental Resultsmentioning
confidence: 99%
“…The next release will thus drastically reduce their frequency through proven methods for reuse of deductions within isomorphic subformulae [6] in order to attain performance competitive with existing tools optimized for the domain.…”
Section: Resultsmentioning
confidence: 99%
“…These range from SMT [19,25,36], deduction [43], level sets [41], and simulation [24] based to flow-pipe construction based methods. In this paper, we compute time-bounded reachability [18] using flow-pipe construction.…”
Section: Related Workmentioning
confidence: 99%
“…x 1 +x 2 + x 3 ≥ 3 represents the same function as the propositional formula x 1 ∧ ¬x 2 ∧ x 3 (we identify propositional formulae with functions). It has been observed that a function can be often represented more compactly as a set of LPBs than as a conjunctive or disjunctive normal form (CNF or DNF) [5][6][7][8]. E.g.…”
Section: Introductionmentioning
confidence: 99%
“…Previous works on LPBs [1,[5][6][7][8] have focused on generalising techniques applied in CNF-based propositional satisfiability solving [12,13,21] to LPBs, emphasising that this is beneficial because of the compactness of LPB representations. Dixon and Ginsberg show that since LPBs are a special case of integer programming, the cutting planes proof system, a standard technique in operations research (OR), can be applied to LPBs.…”
Section: Introductionmentioning
confidence: 99%